Upaya Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran PKN Melalui Model Pembelajaran Kooperatif TGT (Team Game Tournaments) Pada Siswa UPTD SDN Blega I - Atthiana Marpa; Budiyono Budiyono; Siti Komariyah (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The problem in the study carried out is that it provides an understanding regarding student learning in Civics learning which is still not good, especially because the teacher only uses the classroom environment and places more emphasis on taking notes from textbooks. In addition, student participation in asking and answering questions during learning activities is still lacking, which makes them less motivated to learn. Using the Teams Games Tournament approach, this study aims to improve Civics learning outcomes and student involvement in the learning process in class IV SDN Blega 1 unit "GOTONG ROYONG". Planning, implementing, observing, and reflecting are the four steps of classroom action learning carried out over two cycles. At SDN Blega 1, the research participants were grade IV students. The authors tested, interviewed, and made observations while developing a data collection methodology. Based on the findings of the data analysis, it was found that students learned more about human collaboration in the Civics curriculum. Whereas in Cycle I 44% of students passed the KKM, and 56% of students did not pass, after being given instructions, Cycle II used the Teams Games Tournament approach to carry out learning achievement tests, so that the number of students who passed increased. 32 people or 89%, while the decrease in the number of students who did not pass was 4 people or 11%, and Cycle III increased the number of students who passed by 36 people or with a percentage of 100%. Civics learning outcomes for class IV SDN Blega 1 can be improved through learning activities with the Teams Games Tournament (TGT) paradigm.